Vitamin D Receptor Gene Polymorphisms Are Associated With Leprosy in Southern Brazil - Pepineli, Afonso Carrasco; Alves, Hugo Vicentin; Tiyo, Bruna Tiaki; Macedo, Luciana Conci; Visentainer, Lorena; de Lima Neto, Quirino Alves; Zacarias, Joana Maira Valentini; Sell, Ana Maria; Visentainer, Jeane Eliete Laguila (Frontiers in Immunology, 2019)
Vitamin D, together with its nuclear receptor (VDR), plays an important role in modulating the immune response, decreasing the inflammatory process. Some polymorphisms of the VDR gene, such as BsmI (G>A rs1544410), ApaI (G>T rs7975232) and TaqI (T>C rs731236) could affect its stability and mRNA transcription activity, while FokI T>C (rs2228570) gives a truncated protein with three fewer amino acids and more efficiency in binding vitamin D. This study evaluated these four polymorphisms in the immunopathogenesis of leprosy in 404 patients and 432 control individuals without chronic or infectious disease in southern Brazil. When analysing differences in the allele and genotype frequency of polymorphisms between patients (leprosy per se, multibacillary and paucibacillary clinical forms) and controls, we found no statistically significant association. Regarding haplotype analysis, the bAt haplotype was associated with protection from leprosy per se (P = 0.004, OR = 0.34, CI = 0.16–0.71) and from the multibacillary clinical form (P = 0.005, OR = 0.30, CI = 0.13–0.70). In individuals aged 40 or more years, this haplotype has also showed protection against leprosy per se and multibacillary (OR = 0.26, CI = 0.09–0.76; OR = 0.26, CI = 0.07–0.78, respectively), while the BAt haplotype was a risk factor for leprosy per se in the same age group (OR = 1.34, CI = 1.04–1.73). In conclusion, despite having found no associations between the VDR gene polymorphisms with the development of leprosy, the haplotypes formed by the BsmI, ApaI, and TaqI polymorphisms were associated with leprosy per se and the multibacillary clinical form.